PENGUATAN KAPASITAS KADER POSYANDU DALAM IMPLEMENTASI INTEGRASI LAYANAN PRIMER - Novika, Revi Gama Hatta; Afifah, Ani; Saputro, Dedi Ari; Damayanti, Emmy; Wandansari, Novia Erliana; Ramadhani, Linda Alfath (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
Primary Health Care Transformation positions health cadres as key actors in implementing Integrated Primary Care (IPC). Although flipcharts are widely used in health education, evidence on their effectiveness in improving cadre readiness for IPC remains limited. This study aimed to assess the effectiveness of flipcharts in increasing Posyandu cadres’ IPC knowledge. A quasi-experimental one-group pre-test–post-test design without a control group was conducted among 30 purposively selected cadres in Sragen Regency in September 2025. IPC knowledge was measured using a structured questionnaire and analyzed with the Wilcoxon Signed Ranks Test. The mean knowledge score increased from 9.17 to 9.97, with a Wilcoxon test result of p = 0.002 (p < 0.05), indicating a significant improvement. These findings support previous evidence on the usefulness of simple visual media in strengthening cadre comprehension. Flipcharts are a practical educational tool to enhance cadre capacity and support IPC implementation at the community level.